The Legal Arrangements of Intellectual Property Rights in Indonesia on Addressing Priority Watch List Status - Manurung, Oktavia Pitta Marito; Sidauruk, Jinner; Situmorang, Samuel FB (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
Intellectual property law enforcement in Indonesia is not a new issue. Indonesia is still included in the Priority Watch List issued by the United States Trade Representative (USTR), which has an impact on the dynamics of international trade, particularly in influencing the decisions of foreign business actors to conduct trade activities in Indonesia. The issues examined in this research include: (1) How intellectual property law, specifically the provisions in Law No. 20 of 2016 concerning Trademarks and Geographical Indications, relate to trademark infringement as stated in the 2024 Special 301 Report by the USTR; and (2) what is the role and responsibility of the Indonesian Government in handling the Priority Watch List status in the 2024 Special 301 Report by the USTR. This research used a prescriptive normative (doctrinal) legal research method, with the aim of providing a comprehensive understanding of legal issues related to trademarks and government responsibilities in the context of international trade. The result show that the role and responsibility of the Indonesian government in addressing priority watchlist status, including raids and raids, conducting international cooperation with INTERPOL, USPTO. Indonesia is also active in implementing socialization and education on the importance of complying with intellectual property laws, to the point of forming an intellectual property task force such as an operational task force (Satgas OPS) to handle complaints of intellectual property violations.